Development of Quality Management Systems for Clinical Practice Guidelines in Korea - Jo, Heui-Sug (J Korean Med Sci, 2015)
This study introduces the Clinical practice guidelines (CPGs) appraisal system by the Korean Academy of Medical Sciences (KAMS). Quality management policies for CPGs vary among different countries, which have their own cultures and health care systems. However, supporting developers in guideline development and appraisals using standardized tools are common practices. KAMS, an organization representing the various medical societies of Korea, has been striving to establish a quality management system for CPGs, and has established a CPGs quality management system that reflects the characteristics of the Korean healthcare environment and the needs of its users. KAMS created a foundation for the development of CPGs, set up an independent appraisal organization, enacted regulations related to the appraisals, and trained appraisers. These efforts could enhance the ability of each individual medical society to develop CPGs, to increase the quality of the CPGs, and to ultimately improve the quality of the information available to decision-makers.